Um Estudo de Politicas e Práticas do uso do GNV no transporte público urbano do Brasil - Cortez, Breno Peixoto (2006)
The use of Natural Gas Vehicle has had a fast increase lately. However, in order to have a continuous success this Program needs to develop converting devices of Otto-cycle engines, gasoline or alcohol, to the use of NGV (Natural Gas Vehicle) that presents low cost, maintaining the same original development of the vehicle and low level of emissions, considering the PROCONVE rules. Due to the need to diversify the matrix in order to avoid energetic dependence and due to strict pollution control, it has increased in the Brazilian market the number of vehicles converted to the use of NGV. The recent regulation of the PROCONVE, determining that the converted engines with kits should be submitted to emission testing, comes to reinforce the necessity of the proposed development. Therefore, if we can obtain kits with the characteristics already described, we can reach a major trust in the market and obtain an increase acceptance of the vehicle conversion for NGV. The use of natural gas as vehicle fuel presents several advantages in relation to liquid fuels. It is a vehicle fuel with fewer indexes of emissions when compared to diesel; their combustion gases are less harmful, with a major level of safety than liquid fuels and the market price is quite competitive. The preoccupation that emerges, and the motivation of this project, is to know which are the main justifications for such technology, well accepted in other countries, with a low index or emission, with a high level of safety, where its maintenance becomes low, reminding that for this it is necessary that this technology has to be used properly, and once available in the market will not motivate interest in the urban transportation companies in Brazil, in research centers in general. Therefore this project exists to show the society in a general way the current vision of the main governmental factors, of the national research centers and of the private companies concerning the use of natural gas vehicles in urban transport vehicles, in order to give a major reliability to the population as well as to motivate national market competitiveness with a low cost and reliable product and to enrich the national technology